2019
DOI: 10.1111/jicd.12474
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Thai version of the Health Literacy in Dentistry scale: Validation among Thai adults with physical disabilities

Abstract: Aim To validate the Thai version of the Health Literacy in Dentistry scale (HeLD‐Th) among Thai adults with physical disabilities. Methods The original Health Literacy in Dentistry (HeLD) was translated into Thai (HeLD‐Th). The final version of the HeLD‐Th was evaluated through a cross‐sectional study of 160 participants in Thailand. Interview questionnaires and oral examination were performed. The reliability and validity of the HeLD‐Th were determined. Results The internal consistency was acceptable, with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…We found that older participants were approximately 1.8 times more likely to have limited OHL (p = 0.035). This finding consists of a study from Thailand, which reported that older adults had inadequate oral health literacy than younger adults (Sermsuti-Anuwat & Pongpanich, 2019). Similar studies also mentioned the shortage of OHL among the elderly; therefore, enhancing oral health literacy is a solution to improve the oral health-related behaviours, oral hygiene practices, satisfaction with oral health, and oral health status of the elderly (Jones, Parker, Mills, Brennan, & Jamieson, 2014;Tenani et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We found that older participants were approximately 1.8 times more likely to have limited OHL (p = 0.035). This finding consists of a study from Thailand, which reported that older adults had inadequate oral health literacy than younger adults (Sermsuti-Anuwat & Pongpanich, 2019). Similar studies also mentioned the shortage of OHL among the elderly; therefore, enhancing oral health literacy is a solution to improve the oral health-related behaviours, oral hygiene practices, satisfaction with oral health, and oral health status of the elderly (Jones, Parker, Mills, Brennan, & Jamieson, 2014;Tenani et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…A study from Australia conducted among 400 Indigenous adults reported that OHL scores were significantly associated with toothbrush ownership, toothbrush use, and dental care accessibility (Jones, Parker, Mills, Brennan, & Jamieson, 2014). A study carried out among Thai independent living adults also revealed that there were substantially significant positive correlations between OHL and toothbrushing behaviours and dental care visiting (Sermsuti-Anuwat & Pongpanich, 2019). In contrast, a research stidied among independent living and assisted living older people by Hjertstedt et al concluded that participants' characteristics and OHL levels could not predict the change of oral hygiene (Hjertstedt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated. We analyzed the proportion value based on a previous study, 21 in which 52.5% of the study participants presented OHL levels higher than the mean. Consequently, the sample size was 361 individuals, assuming a two-sided test and a significance level of less than 0.05 with a power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…A study from Spain has reported that persons with physical disabilities required specific assistance for improving gingival health status 22 . The oral health of Thai people with disabilities is affected not only by their disabilities and limited oral health literacy but also by physical and other barriers to accessing dental care services 5,23–25 . Consequently, normalizing daily oral hygiene is necessary to reduce gingivitis in these populations 6,26 …”
Section: Introductionmentioning
confidence: 99%